Women's empowerment through capacity building enduring efforts in Bangladesh - Bose, Ashish; Monawar Hosain, G. M.; Chowdhury, Kanan; Burman, Bina Roy; Mannan, M. A.; Hosain, Luna; Suya, Satya; Gonoprokashani (New Delhi, India Saṁskr̥iti, 2005)
On economic development of rural women of Bangladesh; a study; also includes case studies.
Includes bibliographical references (pages [178]-179) and index.
Keywords: Women in development -- Bangladesh; Rural women -- Bangladesh -- Economic conditions; Women in development -- Bangladesh -- Case studies